Pelatihan Penggunaan Media Pembelajaran Tentang Budaya Keris Berbasis Virtual Reality di Sekolah Dasar - Rizqi Fitri Naryanto; Mera Kartika Delimayanti; Ranu Iskandar; Didik Supriadi; Imam Sukoco; Aldias Bahatmaka; Warsiti Warsiti (TAAWUN, 2023)
The utilization of Virtual Reality (VR) technology for educational purposes, namely in instructing Indonesian culture, particularly the Keris culture, holds significant importance. This is due mainly to the limited dissemination of knowledge on Keris and traditional weaponry inside educational institutions, as they are not currently incorporated into the curriculum. The Universitas Negeri Semarang and Politeknik Negeri Jakarta teams have developed interactive learning media focusing on virtual reality (VR) technology. The primary objective of the virtual reality (VR) application is to provide a comprehensive exploration of Keris culture, intending to foster a deeper understanding and appreciation of Indonesia's rich cultural legacy among the younger generation, mainly elementary school pupils. The approach involves offering instructional sessions to students and educators, focusing on utilizing virtual reality (VR) technology as an educational instrument. Training activities were provided at Barusari 02 Elementary School in South Semarang. Considering technological accessibility is crucial to ensuring that all students can access educational materials without obstacles. The findings derived from administering pre- and post-assessments to primary school children indicate that Virtual Reality Technology has the potential to engender greater interest among pupils in acquainting themselves with Indonesian culture. Most participants, above 80%, expressed a strong positive inclination towards utilizing Virtual Reality (VR) Technology to acquire knowledge about various cultural aspects. By providing appropriate support and adopting a comprehensive approach, virtual reality (VR) has the potential to serve as an efficacious instrument for enhancing students' comprehension and admiration of Indonesian culture.